The de(con)struction of the history of Spain or spanish historiographic metafiction: Antonio Orejudo Utrilla's "Fabulosas narraciones por historias" - Lozano Mijares, Pilar (Tropelías: Review of Literary Theory and Comparative Literature, 2021)
The goal of the latest historical novel (also called historiographical metafiction) in Spain is to “de(con)struct”, that is to say, to interpret again and even to destroy the official history, and not so much to reconstruct it. This goal is directly related to the aesthetic paradigm to which it belongs: the postmodernism. At the same time, it is realist in a broader sense, as it mimetises the plural ontology of the advanced industrial societies, in which reality is not a stable concept any more, but it is identified with fiction. This is what Fabulosas narraciones por historias, by Antonio Orejudo Utrilla (1996), shows: the author turns the history of Spanish literature upside down and rallies for the postmodern historical revisionism, at the same time as he offers us a very critical glance at Occident past.